Q. 7 A33.7( 7 Votes )

If <span lang="EN

Answer :

Formula used.


(a-b)3 = a3-b3-3ab(a-b)


If x = 2 + √3


Then;



Simplifying it we get;



= = 2-√3


x – = 2 + √3 – [2 - √3]


= 2√3


(x – )3 = x3- 3-3 × x × × (x – )


(x – )3 = x3- -3 × 1 × (x – )


(2√3)3 = x3- -3 × (2√3)


x3 - = 24√3 + 6√3


x3 - = 30√3


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

In each of the foWest Bengal Board - Mathematics

If <span lang="ENWest Bengal Board - Mathematics

If we subtract <sWest Bengal Board - Mathematics

Let us write a raWest Bengal Board - Mathematics

Let us rationalizWest Bengal Board - Mathematics

Let us write the West Bengal Board - Mathematics

Let us write whetWest Bengal Board - Mathematics

Let us fill up thWest Bengal Board - Mathematics

Let us divide firWest Bengal Board - Mathematics

The product of <sWest Bengal Board - Mathematics